2011
DOI: 10.1063/1.3670330
|View full text |Cite
|
Sign up to set email alerts
|

Strain enhanced electron cooling in a degenerately doped semiconductor

Abstract: Enhanced electron cooling is demonstrated in a strained-silicon/superconductor tunnel junction refrigerator of volume 40 um^3. The electron temperature is reduced from 300 mK to 174 mK, with the enhancement over an unstrained silicon control (300 mK to 258 mK) being attributed to the smaller electron-phonon coupling in the strained case. Modeling and the resulting predictions of silicon-based cooler performance are presented. Further reductions in the minimum temperature are expected if the junction sub-gap le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…The use of strained silicon reduces the constant R by a factor of 25 compared to unstrained silicon, 19 this results in a corresponding improvement in the second term of Eq. (5) (the phonon noise).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of strained silicon reduces the constant R by a factor of 25 compared to unstrained silicon, 19 this results in a corresponding improvement in the second term of Eq. (5) (the phonon noise).…”
mentioning
confidence: 99%
“…where R is a material constant that has been measured 19 to be 2 Â 10 7 W K -6 m -3 ; X is the volume of the bolometer's absorber; T ph and T e are the phonon and electron temperatures, respectively, and the power b has been found 19 to be 6. From this, we can define a thermal conductance, G, from the phonons to the electrons as…”
mentioning
confidence: 99%
“…It has been shown that introducing strain into the silicon lattice can further reduce this coupling, allowing microrefrigerator-type devices to achieve lower electron temperatures compared to unstrained-silicon [4].…”
Section: Introductionmentioning
confidence: 99%
“…7 Metal-semiconductor tunnel junctions have been utilized in low-temperature microcoolers for effective electronic cooling down to 40 mK through hot quasiparticle tunneling. [8][9][10][11] So far, there have been no attempts to extend use of Schottky junctions to other types of low temperature tunneling devices. In the present Letter, we report on a CBT sensor with Schottky barrier tunnel junctions fabricated on a heavily doped silicon-on-insulator (SOI) film.…”
mentioning
confidence: 99%
“…10,17,18 Weak electron-phonon coupling due to the strong temperature dependence in Eq. (6) is very well known to be the bottleneck in the heat transfer below 1 K that effectively precludes electrons from reaching full thermal equilibrium with phonons, especially in the millikelvin range.…”
mentioning
confidence: 99%